The Impact of Sustainability and Corporate Social Responsibility in Current and Future Literature. Two Responses to Bring Innovation and Competitive Advantages to Companies - Teodora NACU; Emilia JERCAN (Communications of International Proceedings, 2022)
Sustainability and Corporate Social Responsibility (CSR) are becoming one of the latest trends of our century, not only in terms of innovation but also for competitive advantages of companies and economies, especially after periods of insecurities such as the economic crisis of 2008 and the COVID-19 pandemic. Becoming a sustainable company means reducing the costs of utilities and cultivating a reliable business image. Moreover, understanding how employees engage in CSR strategies and actions determine business longevity and productivity. Today, the idea behind the concept of sustainability offers growth and progress and initiates economic development for the companies and generally for the economic systems. This paper focuses on the impact of sustainability and CSR in academic literature while observing its evolution over the years and predicting its future trends. Moreover, analyzing academic literature gives future responses while bringing innovation and competitive advantages for companies. The contribution of this paper consists of giving concrete inputs for economic stakeholders, policymakers or for the Academia. Finally, this paper predicts the impact of concepts such as Sustainability and Corporate Social Responsibility in the economic literature thanks to tools such as Python.
Keywords: Sustainability; Corporate Social Responsibility; Innovation; Competitive Analysis